COMPARATIVE RESULTS OF SURGICAL TREATMENT OF PRIMARY ECHINOCOCCOSIS OF THE LIVER - D.S., Sapaev; F.R., Yakubov; S.S., Yakhshiboev (PT. Antis International Publisher, 2024)
Despite the large number of methods of antiparasitic treatment of the cyst cavity, the frequency of complications and relapses remains almost at the same level. The comparative analysis was carried out taking into account the study of the results of the immediate period, the long-term period and the assessment of the quality of life after various types of echinococcectomy. When analyzing the average duration of the operation and the duration of the hospital period, it was noted that in the main group, the duration of the operation on average corresponded to 120.8 minutes, and in the comparison group-104.2 minutes. The proposed tactical aspects of surgical treatment of EP, taking into account the peculiarities of physical and chemical treatment of the residual cavity and the extended use of its elimination by complete or partial suturing, including large or complicated cysts, reduced the need for drainage of the residual cavity from 63.8% to 36.6%.